ҲАКИМ ТЕРМИЗИЙНИНГ ТАБИАТ ЎЗГАРИШЛАРИНИНГ ИНСОН РУҲИЯТИГА ТАЪСИРИ ХУСУСИДАГИ ҚАРАШЛАРИ - Қодирова, А.Б. (SCIENCE and SOCIETY, 2020)
At the end of his life, al Khakim at-Termizi was engaged in secular science. The scholar adhered to the ideas and beliefs of mysticism in his research’s. The material world is a product of the spiritual world and it’s glitters, namely, the material world is inextricably linked with the objects, forms, knowledge which confirms the existence of the spiritual world, its substance (nature, society, animals, plants); to understand the spiritual realm; It is also necessary to understand the process which means to remove the veil between man and God, and to direct man to the spiritual realm.